Implementasi Manajemen Konflik Intrapersonal dan Interpersonal oleh Murobbi bagi Santri Pondok Pesantren - Mustafidin, Ahmad; Wahyudi, Andi; Ambari, Muhammad Zaki (Jawda: Journal of Islamic Education Management, 2024)
The main goal of Islamic education is to form good morals or character. The rapid development of technology has become a new chapter in efforts to develop an Islamic education system so that it can always follow the flow of developments. In the current era of globalization, it has become a necessity for Islamic educational institutions to update educational services according to the needs of the times. Ideally, Islamic educational institutions in the 21st century must follow the flow of developments and not abandon the concept of traditional Islamic education (pesantren). In this case, education cannot be separated from the role of a teacher or murobbi as the spearhead of the Islamic education system. In Islamic education, we know the term murobbi as a physical and spiritual educator. This study will discuss, 1) how to identify intrapersonal and interpersonal conflicts in the Darul Amanah Bedono Islamic boarding school? 2) how is the implementation of intrapersonal and interpersonal conflict management in the Darul Amanah Bedono Islamic boarding school? This study uses a qualitative descriptive method, where this method is used to present in-depth information related to the implementation of murobbi intrapersonal and interpersonal conflict management for students. The results of this study illustrate that the murobbi system is easier to implement intrapersonal and interpersonal conflict management, including the following; Intrapersonal conflict management begins with identifying individual problems of students, including; pessimistic, unfocused, bored, loss of motivation, undisciplined, confused, needing adjustment, and lazy. While conflict management or problem solving that is applied includes; providing motivation, conducting summons, focus training, outings, and refreshments. The application of interpersonal conflict management is carried out by identifying conflicts between students such as; physically insulting each other, belittling parents' work, insulting appearance, and offending feelings. While the problem solving that is applied includes; socialization, summons, coaching, confrontation, motivation, time discipline, direction, games, discussions, mutual respect, education, respect, and providing understanding. This study opens up opportunities for researchers such as lecturers and students as well as the community who need the results of research that has been conducted on research topics that are relevant to this study. It is hoped that for the sake of progress in the field of research, further researchers can use different research methods, or explore other relevant and objective variables.